"On the doctor's orders": A pilot study of the effects of website marketing for medical specialist providers under gatekeeping arrangements. Issue 4 (2nd October 2017) - Zwier, Sandra
ABSTRACT: Websites from medical specialist providers are becoming increasingly marketing oriented, but there exists a paucity of empirical research on the effects. This experimental study explored effects of exposure to real websites from medical specialist providers among Dutch adults under physician gatekeeper arrangements. Exposure led to a stronger intention to seek treatment from the specialist provider and motivation to rely on the providers' claims. Weaker to absent effects were found for intention to question the physician gatekeeper's referral and this was chiefly motivated by the belief that "the doctor knows best." Implications for specialist provider marketing under gatekeeping arrangements are discussed.